Environmental impact of greenhouse tomato production strategies using life cycle assessment approach (2009)
In Colombia, greenhouse tomato (Solanum lycopersicum L.) production has been increasing during the last years. Greenhouse production has caused landscape changes, ecosystem flux variations and risings on energy inputs and residue generation. The aim of this work was to quantify the relative intensity of energy demand, resources consumption and pollutants emissions to air, soil and water as a consequence of the implementation of technological alternatives for greenhouse tomato production. Life cycle assessment (LCA) approach was applied to determine the environmental sustainability of tomato production chain. Three strategies were evaluated: soil production system under single layer plastic greenhouse (SSP), substrate production system under double layer plastic greenhouse (HDP) and HDP including heating (HDPH). The Tomgro model was used to determine biomass production for each crop cycle under the three strategies. Potential impact of infrastructure and its contribution to environmental loads were determined especially for categories: climate change, eutrophication and marine aquatic ecotoxicity. LCA results showed the lowest energy consumption for SSP strategy, followed by HDP, while HDPH registered the highest energy demands. The major impact of greenhouse tomato production on the aforementioned categories is related to leaching for SSP and HDP, while, for HDPH, fuel consumption causes the highest environmental impact. Biodegradable residues are of major importance since they lower the impacts for all categories. Water pollution and eutrophication are affected by high nutrient emissions. LCA approach and the use of simulation models allowed assessing the environmental impact of production strategies and possible effects of technological improvements on commercial production systems.